Facing challenges and complexities in retention of novice teachers - McDonald, Denise Tutka (Emerald Publishing Limited : Information Age Publishing Inc., 2019)
"The chapters in the book present in-depth examination of novice teachers' experiences in Houston area schools during their first-through-third year of teaching. Their professional challenges and the unique conditions in which they must navigate their developing and sometimes fragile teacher identity are comprehensively explored"-- Provided by publisher.
Keywords: Teacher turnover -- Texas -- Houston -- Prevention.; Employee retention -- Texas -- Houston.; First year teachers -- In-service training -- Texas -- Houston.; Teachers -- In-service training -- Texas -- Houston.; Education -- Administration -- General.; Educational administration and organization.; elektronické knihy; electronic books